PENGARUH FAKTOR FUNDAMENTAL MAKRO TERHADAP INDEKS HARGA SAHAM GABUNGAN (Studi pada Bursa Efek Indonesia Tahun 2007-2012) - Agus Suharno; MG. Kentris Indarti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
The objective of this research is to empirically examine about the factors affecting the Composite Stock Index in Indonesia Stock Exchange. The factors are SBI Rate, World Oil Price, World Gold Price, and Exchange Rate of Indonesia Rupiah. The sample of this research is monthly data of the SBI Rate, World Oil Price, World Gold Price, Exchange Rate of Indonesia Rupiah, and Composite Stock Index from October, 2007 until September, 2012. This research uses multiple regression analysis.The result of this research shows that the SBI Rate negatively affect the composite stock indeks (IHSG), while the world oil price and world gold price positively affect the IHSG. But, the exchange rate of Indonesia rupiah is not affect the IHSG. The value of adjusted R square is 0.519%. This means that 51.90% IHSG movement can be predicted by the movement of the four independent variables. Keywords: sbi rate, world oil price, world gold price, exchange rate of indonesia rupiah, IHSG